Effect of Paitan Compost Fertilizer and Corn Rooting Rhizobakteri on the Growth and Yield of Glutinous Corn (Zea mays L. ceratina) - Indratmi, Dian; Roeswitawati, Dyah; Firdaus , Tamara (Journal of Tropical Crop Science and Technology, 2024)
Glutinous rice corn crops in Java show low productivity despite their potential. Agricultural land issues in Indonesia, such as soil fertility and excessive use of inorganic fertilizers, persist. Tithonia diversifolia plants are utilized for composting to address these concerns. Additionally, corn root microorganisms act as biological fertilizer, enhancing plant growth. This study aims to investigate the interaction between Tithonia compost dosage and corn root Rhizobacteria on glutinous corn growth and yield. Conducted in two locations—laboratory for Rhizobacteria isolates and field for composting and planting—the research employed a Divided Plot Design with 36 treatment combinations. Observations included plant height, stem diameter, leaf area, cob count, cob diameter, cob weight, and cob length. Results indicate interaction effects between Rhizobacteria and compost dosage on leaf area growth at 28 days post-planting. Additionally, there's an impact on stem blight intensity at 42 days post-planting. Rhizobacteria dosage didn't significantly affect plant growth or cob yield parameters. However, paitan compost dosage influenced plant height, stem diameter, and cob count, with the best response seen at 14 tons/ha dosage.